Hospital-Acquired Conditions: A Review of Classical and Novel Risk Factors Following Total Hip and Knee Arthroplasties. Issue 7 (July 2021) - Crespi, Zachary; Ismail, Aya; Awad, Mohamed E.; Hasan, Ahmad I.; Irfan, Furqan B.; Jaffar, Muhammad; El-Othmani, Mouhanad M.; Saleh, Khaled J.
Abstract : In 2016, a total of 48, 771 hospital-acquired conditions (HACs) were reported in U.S. hospitals. These incidents resulted in an excess cost of >2 billion, which translates to roughly 41, 000 per patient per HAC. In the settings of total hip arthroplasty (THA) and total knee arthroplasty (TKA), increased age, a body mass index of >35 kg/m2, male sex, diabetes mellitus, electrolyte disturbances, and a history of anemia increase the likelihood of surgical site infections. Institution-specific (surgical) risk factors such as increased tourniquet time, an operative time of >130 minutes, bilateral procedures, a femoral nerve block, and general anesthesia increase the risk of HACs in the settings of THA and TKA.